Physical Activity Level Influences MTHFR Gene Methylation Profile in Diabetic Patients - Diniz, Tainá Gomes; Silva, Alexandre Sérgio; dos Santos Nunes, Mayara Karla; Ribeiro, Mateus Duarte; Filho, João Modesto; do Nascimento, Rayner Anderson Ferreira; Gomes, Cecília Neta Alves Pegado; Evangelista, Isabella Wanderley de Queiroga; de Oliveira, Naila Francis Paulo; Persuhn, Darlene Camati (Frontiers in Physiology, 2021)
Introduction MTHFR methylation status is associated with microvascular complications in diabetes, but the factors influencing this profile remain unknown. Objective The aim of this study was to evaluate the influence of physical activity level and nutritional status on the methylation profile of the MTHFR gene in patients with type 2 diabetes mellitus (T2DM). Methods A total of 111 patients, 43 men and 68 women diagnosed with DM (7.0 ± 2.3 years), answered the International Physical Activity Questionnaire (IPAQ) and underwent blood collection for biochemical analysis, DNA extraction, and MTHFR gene methylation profile determination. Result The comparison of the methylation pattern showed that the partially methylated profile predominates in the insufficiently active group (85%), which does not occur in the sufficiently active group (54%) (p = 0.012). No differences were found in the nutritional status comparison. Logistic regression including overweight, waist circumference, gender, age, time of DM, hypertension, dyslipidemia, smoking, alcoholism, and family DM revealed that the association of the level of physical activity with methylation profile proved to be independent of these confounding variables. Considering the partially methylated profile as a result, being physically inactive favors the partially methylated MTHFR pattern in patients with DM. Conclusion We concluded that insufficient physical activity is associated with partially methylated pattern of MTHFR promoter.